ANALISIS KUANTITATIF: WAKTU TUNGGU DAN KEPUASAN PASIEN TERHADAP PELAYANAN RAWAT JALAN RS HASTA HUSADA KEPANJEN: Quantitative Analysis: Waiting Time and Patient Satisfaction with Outpatient Services at Hasta Husada Kepanjen Hospital - Prisusanti, Retno Dewi; Kurniawan, Fendi; Akhmad, Mauludin (Forind Press, 2024)
Long queues continue to plague healthcare services, and one of the main causes of dissatisfaction is long waiting times. Patient waiting times are a significant factor in determining the quality of healthcare. Based on preliminary research at RS HASTA HUSADA Kepanjen, it appears that the implementation of outpatient services is not yet running optimally, especially for long-term outpatients. To investigate the factors contributing to long waiting times in outpatient services at RS HASTA HUSADA Kepanjen, with a particular focus on long-term outpatients, and to identify strategies for improving patient flow and reducing waiting times. This study used a descriptive type with a quantitative approach and a cross-sectional design. The sampling technique used is purposive sampling. The research instruments used include questionnaires, observation checklists, and time observation assessments. Data analysis was carried out using univariate analysis and bivariate analysis with chi-square test. The average patient at HASTA HUSADA HOSPITAL Kepanjen had to wait 70.18 minutes to get outpatient services, and most of the time was relatively long (more than 60 minutes). However, the level of patient satisfaction is classified as